Jaminan Tenurial dalam Kebijakan Perhutanan Sosial: Kasus Skema Perhutanan Sosial di Perhutani, Kabupaten Malang, Jawa Timur - Ramli Ramadhan; Alvin Naharul Riski; Mochamad Chanan (Jurnal Ilmu Kehutanan, 2024)
The Social Forestry Program was a government initiative that yielded significant outcomes and provided unprecedented access and opportunities to the community. One notable change has occurred in the Perhutani area through a scheme known as IPHPS. This scheme provides long-term tenure security to forest farmers with higher returns than before. In addition, extensive experience in addressing tenure conflicts in the Perhutani area, a State Forestry Corporation (SFC), has prompted communities to apply for the IPHPS scheme. Therefore, this research aimed to investigate the dynamics of changes in access and assess their implementation using the concept of property rights as a framework. The results showed that the IPHPS scheme provided community groups the right to manage forests but needed more flexibility to decide on the use of resources. In addition, the management patterns regulation had a significant responsibility to restore forest conditions. Furthermore, this research proposed new rights, particularly management rights, for community groups to manage their forest resources up to the operational level and improve forest conditions. In addition, the absence of a management authority caused difficulties in achieving social forestry's objective of increasing local communities' role in managing their forest resources.